COMPARATIVE STUDY ON REPRODUCTIVE PERFORMANCE OF BLACK AND YELLOW-FOOTED CHINESE INDIGENOUS GOOSE (SHITOU GOOSE) UNDER OFF-SEASON PRODUCTION CONDITIONS - Y. Guo; Z. H. Zhao; R. S. Huang; X. Q. Chen; L. X. Li; B. Balasubramanian; R. M. Jia1; W. C. Liu1 (Journal of Animal and Plant Sciences, 2020)
The present study was conducted to compare the reproductive performance of black and yellow-footed Chinese indigenous goose, Shitou goose. A total of 890 two-year-old black-footed Shitou geese and 410 two-year-old yellow-footed Shitou geese were selected to carry out off-season feeding experiment to observe the eggs production, the law of laying eggs and the changes of body weight. The experiment time is one year. The results showed that the body weight of black-footed Shitou geese was less than that of yellow-footed Shitou geese, and the difference in body weight between male and female geese was very significant in February, April and June (P < 0.01). After entering the breeding period, with the extension of the laying period, the body weight of female geese and the weight difference among breeds gradually decreased. However, the body weight of male geese did not change significantly during the breeding period. Meanwhile, the egg production of these two kinds of geese was not high. The number of qualified eggs produced by black-footed Shitou geese and yellow-footed Shitou geese was 32.46 and 28.66 respectively, and the corresponding breeding period was 301 days and 263 days, respectively. In addition, both species of geese have four egg production peaks during the breeding period. The laying time of black-footed Shitou geese was mainly concentrated in May, June, July, August and December and the monthly laying rates were 13.07%, 21.06%, 14.14%, 16.74% and 16.05%, respectively. The average laying rate during the breeding period was 11.59%. The laying time of yellow-footed Shitou geese was mainly concentrated in April, May, June, July and August and the monthly laying rates were 8.78%, 10.52%, 15.76%, 7.08% and 6.20%, respectively. The average laying rate during the breeding period was 10.60%. Moreover, the weight changes of female geese of the two species of geese have the same law, that is, after entering the breeding period, the body weight gradually decreases with the extension of the laying period. However, the change of body weight of male geese during breeding period was not obvious. Taken together, the average egg production and egg laying rate of black-footed shitou geese are higher than that of yellow-footed Shitou geese. In addition, black-footed Shitou goose are more popular in the market in Leizhou Peninsula, so it is more suitable to raise black-foot Shitou goose in Zhanjiang area.
Keywords: Black-Footed Shitou geese; Yellow-Footed Shitou geese; egg production performance; weight change; off-season